Antibiotic Resistance in Aquatic Systems - Amy Pruden; Satoru Suzuki; Tong Zhang; Marko Virta (Frontiers Media SA, 2017)
Rivers, lakes and the ocean receive antibiotic resistance genes from human environments. The aquatic environments are a huge reservoir and exchange stage of antibiotic resistance genes.
English
Keywords: Gene reservoir; aquatic environment; Resistance enhancement factor; horizontal gene transfer